Born to Win: Reproductive Health Policy and Urban Education Returns in China - Gao, Qing; Ren, Xiu-Xiu; Yan, Wei-Lan; Wang, Ai-Hua; Zhang, Wei-Hua (Frontiers in Public Health, 2022)
This paper explores the relationship between China's reproductive health policy and the rate of return on urban education by using fixed effect, mediating effect and breakpoint regression models. To study the impact of China's reproductive health policy on individual years of education, income and return on education. The impact of reproductive health policy on population health and overall human development. The empirical results show that the implementation of China's reproductive health policy can improve the rate of return on urban education and increase the average length of education of urban residents by 0.29 years. Under the breakpoint regression model, the educational return rate of urban residents is about 12.2%, higher than the OLS estimate. On the one hand, China's reproductive health policy has significantly promoted the return rate of residents' education, and on the other hand, it has effectively promoted the income of urban residents. With the development of economy, the government should properly adjust the reproductive health policy, improve the population health rate, so that the adjustment of the reproductive health policy can comprehensively promote the health of residents at all ages. The overall relaxation of family restrictions on children's human capital investment will likely reduce the negative impact of the overall relaxation of family planning, not only improve the health of the population, but also contribute to sustainable economic development.